2019 Chinese Hypertension League guidelines on home blood pressure monitoring. Issue 3 (31st December 2019) - Wang, Ji‐Guang; Bu, Pei‐Li; Chen, Lu‐Yuan; Chen, Xin; Chen, Yuan‐Yuan; Cheng, Wen‐Li; Chu, Shao‐Li; Cui, Zhao‐Qiang; Dai, Qiu‐Yan; Feng, Ying‐Qing; Jiang, Xiong‐Jing; Jiang, Yi‐Nong; et al.
Abstract: In China, automated blood pressure monitors have been readily available for home use. Home blood pressure monitoring has been indispensable in the management of hypertension. There is therefore a need to establish guidelines for home blood pressure monitoring on the basis of the 2012 consensus document. In this guidelines document, the committee put forward recommendations on the selection and calibration of blood pressure measuring devices, the frequency (times) and duration (days) of blood pressure measurement, and the diagnostic threshold of home blood pressure.